2021
DOI: 10.3390/nano12010099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbon Nanomaterials Dispersions: Can Metal Decoration of MWCNTs Improve Their Physicochemical Properties?

Abstract: A suitable dispersion of carbon materials (e.g., carbon nanotubes (CNTs)) in an appropriate dispersant media, is a prerequisite for many technological applications (e.g., additive purposes, functionalization, mechanical reinforced materials for electrolytes and electrodes for energy storage applications, etc.). Deep eutectic solvents (DES) have been considered as a promising “green” alternative, providing a versatile replacement to volatile organic solvents due to their unique physical-chemical properties, bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…According to Table 2, with increasing temperature there is a decrease in viscosity and consequently an increase in the ionic conductivity, which is in agreement with several papers already published [41][42][43][44][45][46]. Shahbaz et al [47] found that the type of salt and HBD along with the mole ratio of both compounds had a significant effect on increasing/decreasing the viscosity and ionic conductivity of the DES.…”
Section: Deep Eutectic Solvent Characterizationsupporting
confidence: 86%
“…According to Table 2, with increasing temperature there is a decrease in viscosity and consequently an increase in the ionic conductivity, which is in agreement with several papers already published [41][42][43][44][45][46]. Shahbaz et al [47] found that the type of salt and HBD along with the mole ratio of both compounds had a significant effect on increasing/decreasing the viscosity and ionic conductivity of the DES.…”
Section: Deep Eutectic Solvent Characterizationsupporting
confidence: 86%
“…Deep eutectic solvents (DESs) present several advantages when compared to aqueous electrolytes, including better electrochemical stability, wider potential windows, less impact on the ecosystem, etc., leading to this innovative class of nonaqueous/dense ionic fluids becoming the electrolytes of choice for supercapacitors [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…31 Fortunately, DES also has good dispersal ability and is widely used as an efficient dispersant for the chemical synthesis of advanced nanomaterials. [32][33][34] Therefore, DES is expected to achieve a double goal of catalysis and dispersion in the synthesis of PVB. Furthermore, DES has excellent reusability performance, which is an important factor for the possibility of its use in large-scale industrial applications.…”
Section: Introductionmentioning
confidence: 99%